Formulasi Strategi Pada PT Bank Pembangunan Daerah Kalteng Cabang Muara Teweh - Sitha, Rae (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2020)
This study aims to determine what factors are the main strengths and weaknesses of PT. RegionalDevelopment Bank of Muara Teweh. To find out what factors are the opportunities and weaknessof PT. Central Kalimantan Regional Development Bank Muara Teweh Branch, Knowing whatstrategies are right to be implemented at PT. Central Kalimantan Regional Development BankMuara Teweh Branch. The research method used in writing this thesis is a descriptive method witha field survey approach. Descriptive method is a method that discusses problems by describingcharacteristics, describing and interpreting them as a conclusion. The purpose of the field surveyapproach is to obtain facts from the symptoms that exist and look for information relevant to thepurpose of the study. From the sum of the TAS (Total Attractiveness Score) on the QSPM matrix,the product innovation strategy is higher than the market penetration and increasing the number ofcustomers, therefore a feasible strategy is to innovate the product, improve service, add or recruitemployees or experts in support product development. Market penetration and productimprovement strategies must also be considered in order to be able to compete with competitors.The results of this study are expected to provide alternative considerations and strategyformulations within the company, which are in accordance with the model or process managementstrategy to obtain business opportunities